2022
DOI: 10.1093/eurheartj/ehac544.653
|View full text |Cite
|
Sign up to set email alerts
|

CardioneuROablation for reflex syncope: efficacy and effects on autonoMic cArdiac regulatioN. The Roman 1 study

Abstract: Purpose To assess the effects of CNA on syncope recurrences in patients with VVS Methods The Roman 1 study was a prospective, randomized, investigator-initiated trial comparing CNA versus optimal standard therapy in patients with asystolic VVS. Patients were included if they had documented symptomatic cardioinhibitory or mixted spontaneous VVS (at least 3 seconds of asystole), frequent and/or severe symptoms (at least one syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A recent randomized controlled trial showed that CNA is superior to nonpharmacologic treatments in patients with cardioinhibitory VVS. 7 Both types of VVS (vasodepressor and cardioinhibitory) were shown to respond in the first description of CNA by Pachon et al, 4 and this was supported by a subsequent study by Aksu et al, 5 in which 31 patients with functional or vagally mediated AV block were successfully treated with CNA. Recent data indicate that the clinical benefit of CNA persists more than 2 years after the procedure.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A recent randomized controlled trial showed that CNA is superior to nonpharmacologic treatments in patients with cardioinhibitory VVS. 7 Both types of VVS (vasodepressor and cardioinhibitory) were shown to respond in the first description of CNA by Pachon et al, 4 and this was supported by a subsequent study by Aksu et al, 5 in which 31 patients with functional or vagally mediated AV block were successfully treated with CNA. Recent data indicate that the clinical benefit of CNA persists more than 2 years after the procedure.…”
Section: Discussionmentioning
confidence: 89%
“…CNA has emerged as an effective therapeutic alternative that may be superior to traditional measures to prevent VVS. 4 CNA involves identifying sites of cardiac parasympathetic ganglia by empirical anatomical localization, high-frequency stimulation, fractionation mapping, 5 computed tomography, 6 intracardiac echocardiography, 7 or 123 I- meta -iodobenzylguanidine imaging followed by radiofrequency ablation of these sites. GP are commonly located near the ostium of the left and right superior pulmonary veins, the ostium of the right inferior pulmonary vein, the inferior septal portion of the right atrium outside the coronary sinus, and between the distal superior vena cava and proximal aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of deceleration capacity (which is an HRA index related to the vagal activity) strengthens this conclusion ( Zheng et al, 2020 ; Tu et al, 2022 ). In the case of cardioinhibitory VVS, the patients after cardioneuroablation treatment had lower mean RR and significantly changed HRV parameters toward parasympathetic withdrawal ( Piotrowski et al, 2022 ). However, other research indicates the usefulness of the heart rate Poincaré plot shape analyses in VVS diagnosis ( Yuan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… 120 Subsequent case reports and uncontrolled studies reported in Europace 121–127 culminated in a randomized, unblinded study that reported high efficacy after a 2-year follow-up. 128 …”
Section: Treatment Of Vasovagal Syncopementioning
confidence: 99%